Impact of job stress on job performance of health worker with work life balance as mediating variable - Arif, Adhy Lutfi; Rivai, Harif Amali; Yulihasri, Yulihasri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The role of health professionals in a country is important to maintain health care society. The needs of health worker significantly increase in-line with the demand of the society towards improving quality of health. Increasing number of patients from day to day demands jobs for health worker also to be increase. That condition will be affecting the job stress level and the work life balance of the health worker which in turn affects their job performance. This research is using the quantitative method, to test hypothesis by using statistical methods. Data analysis technique in this research using the Structural Equation Model (SEM) by using software Smart PLS 3.0. In this research job stress and work life balance found to significantly affect job performance of health workers, and job stress found to significantly affect work life balance. This research also found the mediation effect of work life balance on the correlation from job stress on job performance.